Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1038/emboj.2013.204
|View full text |Cite
|
Sign up to set email alerts
|

Unlimited in vitro expansion of adult bi-potent pancreas progenitors through the Lgr5/R-spondin axis

Abstract: Lgr5 marks adult stem cells in multiple adult organs and is a receptor for the Wnt-agonistic R-spondins (RSPOs). Intestinal, stomach and liver Lgr5+ stem cells grow in 3D cultures to form ever-expanding organoids, which resemble the tissues of origin. Wnt signalling is inactive and Lgr5 is not expressed under physiological conditions in the adult pancreas. However, we now report that the Wnt pathway is robustly activated upon injury by partial duct ligation (PDL), concomitant with the appearance of Lgr5 expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

16
597
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 583 publications
(638 citation statements)
references
References 65 publications
16
597
1
1
Order By: Relevance
“…Lgr5 + cells in the GER do not contribute significantly to the regeneration of IBCs and IPhCs, a surprising result given that Lgr5 is a marker of stem cells in other tissues (59)(60)(61)(62) and that Lgr5 + cells proliferate and transdifferentiate into HCs after genetic manipulations in the neonatal organ of Corti (34,38,40). However, we found that other cells in the GER, targeted with GlastCreER T induced with tamoxifen at P0 and P1, are required for the replacement of at least a fraction of IBCs/IPhCs.…”
Section: Discussionmentioning
confidence: 99%
“…Lgr5 + cells in the GER do not contribute significantly to the regeneration of IBCs and IPhCs, a surprising result given that Lgr5 is a marker of stem cells in other tissues (59)(60)(61)(62) and that Lgr5 + cells proliferate and transdifferentiate into HCs after genetic manipulations in the neonatal organ of Corti (34,38,40). However, we found that other cells in the GER, targeted with GlastCreER T induced with tamoxifen at P0 and P1, are required for the replacement of at least a fraction of IBCs/IPhCs.…”
Section: Discussionmentioning
confidence: 99%
“…However, in other cases, such as Lgr5 + cells isolated from pancreatic ducts, no insulin-producing cells are found in long-term organoid cultures, indicating the requirement for additional extrinsic factors or intrinsic reprogramming (11). To determine whether any mature taste receptor cells are produced in organoids derived from Lgr5 + cells, we performed double or triple immunostaining of cultured organoids, using antibodies against the taste signaling components gustducin (G protein for sweet, bitter, and umami signaling), T1R3 (taste receptor type 1 member 3, a common subunit of the sweet T1R2/T1R3 and the umami T1R1/T1R3 taste receptor) (23)(24)(25), and carbonic anhydrase 4 (CA4; a marker of sour taste cells) (26).…”
mentioning
confidence: 99%
“…Lgr5 is also known to mark actively cycling stem cells in small intestine, colon, stomach, and hair follicle, as well as quiescent stem cells in liver, pancreas, and cochlea (8). Isolated Lgr5 + adult stem cells from multiple tissues are able to generate so-called organoid structures ex vivo (9)(10)(11). For instance, Sato and colleagues (10) developed a 3D culture system to grow crypt-villus organoids from single intestinal stem cells; all differentiated cell types were found in these structures, indicating the multipotent nature of these cells.…”
mentioning
confidence: 99%
“…49 Drug discovery today is at a crossroads: while increasingly large and 50 varied compound libraries are synthesized and tested in primary 51 screens, the promise of the identified lead compounds remains largely 52 unrealized. Indeed, while tremendous investments in automation 53 have enabled the costs and turnaround time for large to medium-scale 54 primary screening to fall significantly [1], the gap between lead com- 55 pound validation and success in the clinic is still wide, suggesting that 56 a process still beset by significant limitations in efficiency.…”
mentioning
confidence: 99%
“…Indeed, there have also been in the last year reports of such diverse 496 organoids as the pituitary gland [52], inner ear [49], pancreas [53,54] …”
mentioning
confidence: 99%